Optimalisasi Pelaksanaan Program Pelayanan Kesehatan Peduli Remaja (PKPR) Di Sekolah Menenggah Atas - Nuari Andolina; Angellisa Lammabue Panjaitan (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Adolescent Care Health Services (PKPR) is one of the health service programs aimed at adolescents in high schools, to realize “healthy adolescents”. The purpose of this study was to optimize the implementation of the Adolescent Care Health Services Program (PKPR) in senior high schools. The implementation method is carried out by conducting a location survey, looking for problems related to PKPR and finding solutions to these problems. The result of youth empowerment is the development of an “optimization of health services” activity plan. This community service activity was attended by all high school students, teachers responsible for student health services, and PKPR health cadres at school. By providing information about optimizing PKPR health services in high schools and conducting health training for students. It is expected that related parties will be more serious and active in implementing the PKPR program by supervising and monitoring and evaluating the PKPR program regularly and continuously and can allocate special funds to support all activities in the PKPR program.